Maharashtra State BoardHSC Arts 12th Board Exam
Advertisement Remove all ads

Using the rule of negation write the negation of the following with justification. p → (p ∨ ∼ q) - Mathematics and Statistics

Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads
Sum

Using the rule of negation write the negation of the following with justification.

p → (p ∨ ∼ q)

Advertisement Remove all ads

Solution

The negation of p → (p ∨ ∼ q) is
∼ [p → (p ∨ ∼ q)] ≡ p ∧ ∼ (p ∨ ∼ q) .......(Negation of implication)
≡ p ∧ [∼ p ∧ ∼ (∼ q)] .....(Negation of disjunction)
≡ p ∧ (∼ p ∧ q) ...........(Negation of negation)

Concept: Negations of Compound Statements
  Is there an error in this question or solution?

APPEARS IN

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×